Implementasi Hybrid Contract pada Pembiayaan Murabahah Bil Wakalah di BNI Syariah Cabang Makassar - Nur Hikmah; Rahman Ambo Masse; Damira (Institut Agama Islam Negeri Parepare, 2020)
Hybrid contract that is collecting two or more contracts in one financing. Murabaha financing product is an example of a financing product that is often compiled with a wakalah contract that aims to make customers free to choose the items needed because the bank is unable to provide all the items customers need. This study discusses the implementation of hybrid contracts in murabaha financing wakalah with a focus of research to determine the provisions of hybrid contracts in murabaha financing wakalah and implementation of the provisions of hybrid contracts murabaha bil wakalah BNI Syariah KC Makassar.This study uses a qualitative method. Primary data in this study were obtained through direct observation and interviews. Whereas secondary data was obtained from literature such as browsers, Makassar Syariah KC Makassar Microfinance financing manuals and examples of murabahah contracts when the BNI Syariah KC Makassar was held.The results of this study indicate that there are terms and conditions for murabaha financing wakalah contained in 22 articles which emphasize starting from financing provisions to settling disputes in murabaha financing wakalah. The implementation of murabaha bil wakalah at BNI Syariah KC Makassar is also not fully in accordance with the provisions of Fatwa DSN-MUI No. 04 of 2000 concerning murabaha because the bank did not explain the purchase price of the murabahah object to the customer so that it violated the provisions of Fatwa DSN-MUI No. 04 of 2000 6 about murabaha.